Risk stratification with echocardiographic biomarkers in heart failure with preserved ejection fraction: the media echo score - Olivier Huttin; Alan G. Fraser; Lars H. Lund; Erwan Donal; Cecilia Linde; Masatake Kobayashi; Tamas Erdei; Jean‐Loup Machu; Kevin Duarte; Patrick Rossignol; Walter Paulus; Faiez Zannad; et al. (ESC Heart Failure, 2021)
Abstract Aims Echocardiographic predictors of outcomes in heart failure with preserved ejection fraction (HFpEF) have not been systematically or independently validated. We aimed at identifying echocardiographic predictors of cardiovascular events in a large cohort of patients with HFpEF and to validate these in an independent large cohort. Methods and results We assessed the association between echocardiographic parameters and cardiovascular outcomes in 515 patients with heart failure with preserved left ventricular (LV) ejection fraction (>50%) in the MEtabolic Road to DIAstolic Heart Failure (MEDIA) multicentre study. We validated out findings in 286 patients from the Karolinska‐Rennes Prospective Study of HFpEF (KaRen). After multiple adjustments including N‐terminal pro‐brain natriuretic peptide (NT‐proBNP), the significant predictors of death or cardiovascular hospitalization were pulmonary arterial systolic pressure > 40 mmHg, respiratory variation in inferior vena cava diameter > 0.5, E/e' > 9, and lateral mitral annular s' < 7 cm/s. The combination of these four variables differentiated patients with <10% vs. >35% 1 year risk. Adding these four echocardiographic variables on top of clinical variables and NT‐proBNP yielded significant net reclassification improvement (33.8%, P < 0.0001) and increase in C‐index (5.3%, a change from 72.2% to 77.5%, P = 0.015) of similar magnitude as the addition of NT‐proBNP on top of clinical variables alone. In the KaRen cohort, these four variables yielded a similar improvement in net reclassification improvement (22.3%, P = 0.014) and C‐index (4.0%, P = 0.029). Conclusions Use of four simple echocardiographic parameters (within the MEDIA echo score), indicative of pulmonary hypertension, elevated central venous pressure, LV diastolic dysfunction, and LV long‐axis systolic dysfunction, independently predicted prognosis and improved risk stratification additionally to clinical variables and NT‐proBNP in HFpEF. This finding was validated in an independent cohort.